Pengaruh Lingkungan Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening Studi pada Kecamatan Tanjung Palas Kabupaten Bulungan - Kapreli Serah; Shine Pintor Siolemba Patiro; Nurmadhani Fitri Suyuthi (Jayapangus Press, 2026)
The public satisfaction index for services provided by Tanjung Palas Subdistrict in 2019 was in the satisfactory category. Work motivation in Tanjung Palas Subdistrict in 2020 and 2021 did not increase. In 2024, the public satisfaction survey showed an increase in the score to 88.91, which is in the good category. This study aims to analyse the influence of the work environment and organisational culture on employee performance with job satisfaction as an intervening variable in Tanjung Palas Subdistrict, Bulungan Regency. The study used a quantitative approach with path analysis through SmartPLS. The research sample consisted of 75 employees using saturated sampling technique. Data were collected through a closed questionnaire that had been tested for validity and reliability. The results showed that the work environment did not have a significant effect on employee performance, either directly or through job satisfaction. Conversely, organisational culture has a significant effect on performance, including through job satisfaction as an intervening variable. In addition, job satisfaction has a positive effect on employee performance. These findings confirm that organisational culture is a dominant factor in improving performance, while the work environment does not have a significant effect. The contribution of this study lies in emphasising the importance of strengthening organisational culture and increasing job satisfaction as key strategies in public sector performance management. These results have practical implications for local governments to build a collaborative, disciplined, and public service-oriented work culture, as well as to create policies that support employee job satisfaction. Given the scarcity of research in sub-district agencies, studies using the intervening variable of job satisfaction are still rare.